Assessment of sphenoid sinus variations and its related neurovasclar structures using contrasted thin slice computed tomography scan of the brain - Amer, Nawal Ahmed Mohamed Ben (Kulliyyah of Medicine, International Islamic University Malaysia, 2018)
The sphenoid sinus is the most variable structure in the human body. The prevalence of these variations' changes according to the population. Due to the sinus location and vital structures related to it, detail knowledge of its anatomical variation is required for optimum patient care. This is a retrospective cross-sectional study measuring the prevalence and describe the variations of sphenoid sinus using thin slice computed tomographic (CT) brain scans for patients aged between 18-60 years at Hospital Tengku Ampuan Afzan (HTAA), Kuantan, Pahang, Malaysia from 1st January to 31st December 2017. A total of 250 brain CT scans was studied for sphenoid sinus pneumatization types, volume, optic nerve relation according to Delano's classification, internal carotid artery (ICA) relation, and the number of the sinus septum and its attachment site. The commonest types of pneumatization were the post sellar type 52%. The mean volume of the sphenoid sinus was 19 cc. Delano's optic nerve Type I was the most frequent type 43% among the study population and mostly seen bilateral. The internal carotid artery in relation to the sphenoid sinus was seen non-protruded in vast frequency 41.6%, protruded ICA in 36.4%, and protrusion with dehiscence in 22% of the study population. Sphenoid sinus with two septa was prominent among the study population (44.3%) and aseptate sinus is seen in 2.4%. The principle attachment site of the septa was sella (28%), internal carotid artery related septa found in 10% of the study population and 3.2% septa attached to optic nerve canal. This research had revealed the presence of sphenoid sinus variations among the study population.